Environmental Sustainability Improvement Of Malang City Based On Local Sustainability - Alifal Hamdan; Ismu Rini Dwi Ari; Imma Widyawati Agustin (Jurnal Sosial Teknologi, 2022)
Background: Malang City is a city that has a function as an area of education, industry, trade, and services so that it is experiencing fairly rapid development. These developments often only pursue economic and social aspects, causing problems in environmental aspects. Research purposes: Assessing the environmental sustainability index in all urban villages in Malang City, analyze the indicators that affect the environmental sustainability index in all urban villages in Malang City and prepare recommendations for improving environmental sustainability in Malang City. Research methods: The method used is Multi-Dimensional Scaling (MDS) through the Rapid Appraisal for Sustainable Development (RAP-SUSDEV) ordination technique approach modified from RAPFISH, which is a sustainability analysis used to determine status and identify sensitive indicators in the process of knowing sustainability. The MDS method can provide stable results compared to multivariate analysis methods such as factor analysis. Research results: The results of the index display indicators that are sensitive or have an effect on sustainability, which are useful as reference materials in compiling recommendations for improving environmental sustainability in Malang City. Conclusion: The urban areas that have the highest environmental sustainability index values are Tasikmadu and Tunggulwulung Urban Villages with very sustainable status. Meanwhile, the kelurahan that has the smallest environmental sustainability index value is Kotalama Urban Village with unsustainable status. The results of the leverage analysis show that the factors that have a significant effect on environmental sustainability are anticipation and mitigation efforts, namely as many as 23 urban villages. Based on the analysis that has been done, the recommendations for improving environmental sustainability in Malang City are prioritized to build anticipation and mitigation efforts such as early warning systems, safety equipment, and signs, and disaster evacuation routes. The prioritized recommendations were taken based on the most recommendations given to 57 urban villages in Malang City.